Serum amyloid A is a soluble pattern recognition receptor that drives type 2 immunity - Smole, Ursula; Gour, Naina; Phelan, Jordan; Hofer, Gerhard; Köhler, Cordula; Kratzer, Bernhard; Tauber, Peter A; Xiao, Xiao; Yao, Nu; Dvorak, Jan; Caraballo, Luis; Puerta, Leonardo; et al. (Nature immunology, 2020)
The molecular basis for the propensity of a small number of environmental proteins to provoke allergic responses is largely unknown. Herein, we report that mite group 13 allergens of the fatty acid-binding protein (FABP) family are sensed by an evolutionarily conserved acute-phase protein, serum amyloid A1 (SAA1), that promotes pulmonary type 2 immunity. Mechanistically, SAA1 interacted directly with allergenic mite FABPs (Der p 13 and Blo t 13). The interaction between mite FABPs and SAA1 activated the SAA1-binding receptor, formyl peptide receptor 2 (FPR2), which drove the epithelial release of the type-2-promoting cytokine interleukin (IL)-33 in a SAA1-dependent manner. Importantly, the SAA1-FPR2-IL-33 axis was upregulated in nasal epithelial cells from patients with chronic rhinosinusitis. These findings identify an unrecognized role for SAA1 as a soluble pattern recognition receptor for conserved FABPs found in common mite allergens that initiate type 2 immunity at mucosal surfaces.
Keywords: dospělí; Animals; respirační sliznice; primární buněčná kultura; přirozená imunita; Immunity, Humoral; Female; interleukin 33; Lung; Adult; ženské pohlaví; receptory lipoxinů; mladý dospělý; myši knockoutované; Allergens; Mice, Knockout; sérový amyloid A; Adolescent; Up-Regulation; antigeny roztočů domácího prachu; lidé; Interleukin-33; Mice; Epithelial Cells; proteiny vázající mastné kyseliny; upregulace; signální transdukce; Aged, 80 and over; Receptors, Lipoxin; kultivované buňky; Asthma; myši; Signal Transduction; Middle Aged; receptory pro formylované peptidy; Cells, Cultured; humorální imunita; Male; modely nemocí na zvířatech; Aged; bronchiální astma; Rhinitis, Allergic; alergická rýma; Receptors, Formyl Peptide; Serum Amyloid A Protein; Young Adult; Immunity, Innate; Antigens, Dermatophagoides; Disease Models, Animal; plíce; alergeny; lidé středního věku; senioři nad 80 let; Respiratory Mucosa; senioři; zvířata; mužské pohlaví; epitelové buňky; mladiství; Primary Cell Culture; Fatty Acid-Binding Proteins; Humans